DIGITALIZATION OF THE ECONOMY AS THE BASIS OF HUMAN CAPITAL POTENTIAL - Ahmadova Akima Amir; Rzayev Mirza Agharza; İsmayilova Lala Hamlet; Muradova Jala Nizami (Academy Review)
Digitalization of the economy is critically important in the era of global changes in the modern world. Like previous technological transformations, the digitalization of the economy is associated with a number of significant changes. The digital transformation of modern society has a profound impact on traditional human capital, as the active adoption of digitalization leads to the intellectualization of labor. In the context of a digitized economy, human capita – its development and level – becomes a key driver of economic growth and national prosperity. Currently, the primary goals of societal development are to ensure economic growth and improve quality of life. These objectives can be achieved through the establishment of a new economic model that fosters the digitalization of the economy. Achieving an economic and technological breakthrough is impossible without addressing the challenge of enhancing the development of human capital. Relevance of the topic. Today, countries around the world are experiencing changes marked by significant risks and opportunities, which are becoming more apparent across all areas of society. New technologies and innovative products are spreading rapidly, and existing business processes and economic models are being refined. The accelerated optimization and modernization of economic structures, along with the expanded use of innovations and the digitalization of the economy, are significantly transforming the quality of human capital. Digitalization has a profound impact on all socio-economic processes, including the development of human capital. Therefore, it is particularly important to examine the role of human capital in the context of a digitized economy, highlighting the relevance of this topic. The purpose of the article. The purpose of this study is to justify the necessity of digitalizing the economy and to assess the role of human capital in this context. To examine the role of human capital within the digitalization of the economy, it is essential to explain its essence, importance, key characteristics, and constituent elements. Additionally, the study aims to explore various aspects of the digital transformation of modern society that influence changes in human capital, while evaluating the role of the knowledge economy and ICT – key components that drive the acceleration of economic digitalization. Considering the role of human capital in this process, one of the primary objectives is to offer recommendations for its development. Research methods. Generalization, grouping, factor analysis, graph analysis, comparative analysis, development dynamics, and economic-statistical methods were the primary research approaches used in the preparation of this article. Scientific innovation. Some pros and cons of the digitalization of the economy were reviewed, with the conclusion that the benefits outweigh the drawbacks. The primary factor for the success of the digitization process is having a sufficient number of highly qualified personnel in relevant positions, along with a system for training specialists with the necessary skills to develop and effectively apply innovative and digital technologies. The key factors influencing the development of human capital – such as the population’s education level, digital literacy, and culture – were also emphasized. Above all, the importance of investing in human capital was highlighted as crucial for achieving these objectives.